FOLLOW ME: REFLECTION ON THE PAPA CASE FRANCISCO AND HIS IMPACT ON SOCIAL NETWORKS SINCE EMOTIONAL MARKETING - Castrillón, Catherine Jaillier (Universidad Pontificia Bolivariana, 2020)
The following article is an exercise of reflection on what has been the impact on social networks Pope Francis in the corresponding leading the Pope and try to understand whether this phenomenon can be classified under the label of Emotional Marketing and advertising period.